Mobility experiments with microrobots for minimally invasive intraocular surgery - Ullrich, Franziska; Bergeles, Christos; Pokki, Juho; Ergeneman, Olgac; Erni, Sandro; Chatzipirpiridis, George; Pane, Salvador; Framme, Carsten; Nelson, Bradley J. (Investigative Ophthalmology & Visual Science, 2013)
PURPOSE. To investigate microrobots as an assistive tool for minimally invasive intraocular surgery and to demonstrate mobility and controllability inside the living rabbit eye. METHODS. A system for wireless magnetic control of untethered microrobots was developed. Mobility and controllability of a microrobot are examined in different media, specifically vitreous, balanced salt solution (BSS), and silicone oil. This is demonstrated through ex vivo and in vivo animal experiments. RESULTS. The developed electromagnetic system enables precise control of magnetic microrobots over a workspace that covers the posterior eye segment. The system allows for rotation and translation of the microrobot in different media (vitreous, BSS, silicone oil) inside the eye. CONCLUSIONS. Intravitreal introduction of untethered mobile microrobots can enable sutureless and precise ophthalmic procedures. Ex vivo and in vivo experiments demonstrate that microrobots can be manipulated inside the eye. Potential applications are targeted drug delivery for maculopathies such as AMD, intravenous deployment of anticoagulation agents for retinal vein occlusion (RVO), and mechanical applications, such as manipulation of epiretinal membrane peeling (ERM). The technology has the potential to reduce the invasiveness of ophthalmic surgery and assist in the treatment of a variety of ophthalmic diseases. ©2013 The Association for Research in Vision and Ophthalmology, Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: In vivo; Intravitreal; Magnetic; Microrobot; Minimally invasive surgery; Untethered; Vitreous; Wireless